REFLECTIONS ON KANT’S VIEW OF THE IMAGINATION (2015)
Abstract The paper elaborates the theory of imagination in Immanuel Kant’s Critique of Pure Reason and Critique of Judgment. From the first Critique to the third Critique, the imagination emerges under different titles such as reproductive, productive or transcendental imagination. The paper shall try to decide whether its functions suggested in the first Critique and its performance in the third Critique are contradictory or developmental with respect to Kant’s critical philosophy.Thus, it will examine of the power and the scope of the imagination in the first Critique and of its status and performance in the third Critique.